Rationale for American Society of Retina Specialists Best Practice Recommendations for Conducting Vitreoretinal Surgery During the Coronavirus Disease-19 Era. (October 2020) - Chao, Daniel L.; Sridhar, Jayanth; Kuriyan, Ajay E.; Leng, Theodore; Barnett, Brad P.; Carlin, Aaron F.; Wykoff, Charles C.; Gayer, Stephen; Mruthyunjaya, Prithvi; Yonekawa, Yoshihiro; Fawzi, Amani A.; Berrocal, Audina M.; et al.
Purpose: This review details the rationale behind recommendations recently published by the American Society of Retina Specialists (ASRS) and outlines best practices for safety of vitreoretinal surgeons and staff while performing vitreoretinal surgery during the coronavirus disease 2019 (COVID-19) pandemic. Methods: The Committee for ASRS Best Practices for Retinal Surgery During the COVID-19 Pandemic reviewed existing evidence and information on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission and risk factors during vitreoretinal surgery. Recommendations were based on best available published data, cumulative clinical experiences, and recommendations and policies from other organizations. The Grading of Recommendations Assessment, Development and Evaluation approach was used to assess the strength of recommendations and confidence in the evidence. These serve as interim recommendations that will be routinely updated given the current gaps of knowledge and lack of high-quality data on this evolving subject. Results: Relevant existing literature related to methods of transmission and ocular manifestations of SARS-CoV-2 are summarized. The data and clinical experiences driving recommendations for preoperative, intraoperative, and postoperative surgical considerations and anesthesia choice as well as considerations for intravitreal injections are provided. Conclusions: Recommendations are provided with the goal of protecting vitreoretinal surgeons and associated personnel from exposure to SARS-CoV-2 during interventional vitreoretinal procedures. This is a rapidly evolving topic with numerous remaining gaps in our current knowledge. As such, recommendations will evolve and the present article is intended to serve as a foundation for continued dialogue on best practices.